MANAJEMEN WALET MUDA FUTSAL AKADEMI KABUPATEN KEBUMEN TAHUN 2012/2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study is to describe how the management process Walet Muda Futsal Academy runs .Research methods used include interviews , observation and documentation. Results of this study are organizational management stewardship , management and handling athlete management coaches in the Walet Muda Futsal Academy have said well . Management infrastructure and management supervisor at Young Swallow Futsal Academy has not been going well . Overall management process Walet Muda Futsal Academy could not be said better. Conclusions of the research results suggested some of the following : (1 ) Walet Muda Futsal Academy as soon as a new recruit competent in the field of organization and coaches , so there is no administrator or coach who doubles duty . ( 2 ) Walet Muda Futsal Academy should pay more attention to the environment in which athletes hang out , athletes' health and nutritional intake in order to maintain the concentration of athletes and fitness athletes . ( 3 ) management of facilities and infrastructure must be managed properly , from the procurement of new facilities and infrastructure , usage , maintenance , record keeping , providing a reserve fund for the infrastructure needs of the sudden . Make comparisons with infrastructure in other places in order to be used as a reference in the provision of next.